2016
DOI: 10.1177/1059840516679710
|View full text |Cite
|
Sign up to set email alerts
|

Density and Proximity of Licensed Tobacco Retailers and Adolescent Smoking

Abstract: Adolescent smoking prevention is an important issue in health care. This literature review describes the theoretical concept of ecological model for adolescent smoking and tobacco retailers and summarizes previous studies on the association between the density and proximity of tobacco retailers and adolescent smoking. We reviewed nine studies on tobacco retailer density and proximity in relation to adolescent smoking, published in peer-reviewed journals between 2004 and 2014. The tobacco retailer density and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 51 publications
1
33
0
2
Order By: Relevance
“…Nous avons effectué des analyses pour dresser un portrait de la situation au Québec Des facteurs tant personnels qu'environne mentaux ont été associés à l'usage des produits de vapotage chez les jeunes 7 et, à l'instar des produits du tabac, certaines études suggèrent que l'accessibilité géo graphique aux lieux de vente de ces produits serait l'un de ces facteurs. En effet, l'accès et la visibilité des produits du tabac, par l'entremise des points de vente, ont été associés à l'usage de ces produits chez les jeunes 8,9 . Il pourrait en être de même pour les produits de vapotage, des études américaines récentes allant dans ce sens 1012 .…”
Section: Résuméunclassified
“…Nous avons effectué des analyses pour dresser un portrait de la situation au Québec Des facteurs tant personnels qu'environne mentaux ont été associés à l'usage des produits de vapotage chez les jeunes 7 et, à l'instar des produits du tabac, certaines études suggèrent que l'accessibilité géo graphique aux lieux de vente de ces produits serait l'un de ces facteurs. En effet, l'accès et la visibilité des produits du tabac, par l'entremise des points de vente, ont été associés à l'usage de ces produits chez les jeunes 8,9 . Il pourrait en être de même pour les produits de vapotage, des études américaines récentes allant dans ce sens 1012 .…”
Section: Résuméunclassified
“…Research which has considered outlet density in school areas has also found a relationship with adolescent smoking (Barnett et al, 2017, Gwon et al, 2016. However, three studies comparing outlet density near adolescents' home and school found an association with smoking for home area only (Shortt et al, 2014, Lipperman-Kreda et al, 2014b, Schleicher et al, 2016), suggesting home environment may matter more.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The study found less evidence of association between tobacco outlets and pathways to smoking than some previous research. This could be because these analyses were completed in different contexts, often within regions and cities in USA (Gwon et al, 2016) rather than at a national level in Scotland.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations